Negeri Sembilan food as a tourist attraction / Nurul Nabilah Zainal - Zainal, Nurul Nabilah (2017)
Negeri Sembilan has unique cuisine by its own. These aspects contributed to the tourism sector to be able to influence people to come to Negeri Sembilan. The main objective of this study is to promote Negeri Sembilan food to the public. Another objective is also being studied to identify the various type of traditional food in Negeri Sembilan and to promote the uniqueness Negeri Sembilan cuisine for tourist. This study used a questionnaire among people in and outside the Negeri Sembilan and interview people around the Negeri Sembilan area. A total of 50 respondents were selected to participate in this study and based on the information obtained, most of them have linked food as a factor to promote food Negeri Sembilan as a tourist attraction. Therefore, food plays an important role in everyday life and also used as a tourist attraction for visitors to Negeri Sembilan. Exposure of Negeri Sembilan food advertising should be studied and implemented in order to attract tourists to come and at the same time can show the identity of Negeri Sembilan. Advertising design proposes a new image, typography and videography as a way to promote foods to Negeri Sembilan as a tourist attraction in the tourism sector.